Microwave photons emitted by fractionally charged quasiparticles - R. Bisognin (Nature Portfolio, 2019)
One of the many intriguing possibilities in strongly interacting quantum systems is the formation of emergent excitations with fractional charges. Here the authors show how the high-frequency noise emitted by a dc-biased quantum point contact can be used to demonstrate charge fractionalization.